The Influence of Leadership Strategies on Curriculum Management in Modern Islamic Boarding Schools - Syaharuddin, Syaharuddin; Citriadin, Yudin (Ibtida'iy : Jurnal Prodi PGMI, 2025)
Research on leadership strategies in curriculum management in modern pesantren is important considering the challenges of Islamic education in the digital era which demands adaptive and innovative governance. This study aims to identify and analyze the most effective leadership strategies in curriculum management in modern pesantren using the Systematic Literature Review approach. This study is a qualitative research with data obtained from Dimensions and Scopus databases. The results of the analysis show that leadership transformation that is adaptive to digitalization is a key factor in improving the quality of educational governance. Effective leadership is characterized by the ability to design a strategic vision, build collaboration with various stakeholders, and encourage the integration of technology in the curriculum management process. This finding confirms that strengthening the capacity of transformative leadership needs to be a priority in the development of modern pesantren in order to be able to respond to the dynamics of educational change in a sustainable manner.